7(x+1)-4(x+3)=x-19

Simple and best practice solution for 7(x+1)-4(x+3)=x-19 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7(x+1)-4(x+3)=x-19 equation:


Simplifying
7(x + 1) + -4(x + 3) = x + -19

Reorder the terms:
7(1 + x) + -4(x + 3) = x + -19
(1 * 7 + x * 7) + -4(x + 3) = x + -19
(7 + 7x) + -4(x + 3) = x + -19

Reorder the terms:
7 + 7x + -4(3 + x) = x + -19
7 + 7x + (3 * -4 + x * -4) = x + -19
7 + 7x + (-12 + -4x) = x + -19

Reorder the terms:
7 + -12 + 7x + -4x = x + -19

Combine like terms: 7 + -12 = -5
-5 + 7x + -4x = x + -19

Combine like terms: 7x + -4x = 3x
-5 + 3x = x + -19

Reorder the terms:
-5 + 3x = -19 + x

Solving
-5 + 3x = -19 + x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1x' to each side of the equation.
-5 + 3x + -1x = -19 + x + -1x

Combine like terms: 3x + -1x = 2x
-5 + 2x = -19 + x + -1x

Combine like terms: x + -1x = 0
-5 + 2x = -19 + 0
-5 + 2x = -19

Add '5' to each side of the equation.
-5 + 5 + 2x = -19 + 5

Combine like terms: -5 + 5 = 0
0 + 2x = -19 + 5
2x = -19 + 5

Combine like terms: -19 + 5 = -14
2x = -14

Divide each side by '2'.
x = -7

Simplifying
x = -7

See similar equations:

| 5(k-3)-7=3k-(2k-1) | | (3x+2)=(2x-5) | | Log(3)*(5x-1)=3 | | 2-(11/n)=-(5/n^2) | | x-1/3=x-7/7 | | 2(3+6x)-5=7(x+8) | | 1050+5y=1050 | | R(x)=x^3+2 | | x^2+6x=28 | | 20b-3b-2=0 | | 3+ln(x+2)=6 | | p(x)=x^2-1 | | 12-h=22 | | 9*-4(2+4x-6)=4 | | 3x+ln(4x)=4 | | 4x^2-120x-124=0 | | 30z-2=22z-6 | | -3/5times-2/3 | | X=1260+(10*Y) | | -3/5•-2/3 | | -8y-18=-24 | | (x+7).4=36 | | 6+-25=-7 | | 4x^2+12x+68=0 | | 6*1.2+7= | | 21+10x-19=7x+30-4x | | 25x-9-18x=19x-7-12x+13 | | 6(1.2)+2= | | 8(6n-4)=(6n-10)+40 | | y=5x^2+8x-4 | | 79-(5x+15)=5(x+4)+x | | 6x2/(4x/y*3y2/2) |

Equations solver categories